OPTIMALISASI PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE JOINT ECONOMIC ORDER QUANTITY (JEOQ) PADA UD PURNAMA JATI JEMBER - Gusminto, Eka Bambang; Musmedi, Didik Pudjo; Kriswardhana, Ariwinata (BISMA: Jurnal Bisnis dan Manajemen, 2021)
This study aims to determine the optimal amount of raw materials inventory needs and the reorder point of raw materials in UD Purnama Jati Jember. UD Purnama Jati Jember is a company engaged in the production of Jember Regency speciality food and souvenirs. Due to not having a standard method, there are problems of raw material inventory in the production process, including overproduction and excess or shortage of raw materials. Data were obtained by interviewing the company owner and observing the company's production process. Data analysis were performed using least square forecasting, JEOQ, safety stock, and reorder points method. The results of the study showed that the optimal raw material needs are 4,644.772 kg of tape, 2,491.411 kg of wheat flour, 3,967.927 kg of egg, 1,439.623 kg of butter, and 3,519.371 kg of sugar. The total inventory cost of raw material is Rp. 281,296,067 indicated a more efficient inventory cost than the previous method. Meanwhile, the amount of raw materials inventory for the reordering point is 417.39 kg of tape, 231.29 kg of wheat flour, 358.88 kg of eggs, 131.78 kg of butter, and 318.99 kg of sugar. Keywords : JEOQ, raw materials control, reorder point, total inventory costs